2014
DOI: 10.1016/j.atmosres.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

A review on regional dynamical downscaling in intraseasonal to seasonal simulation/prediction and major factors that affect downscaling ability

Abstract: Regional climate models (RCMs) have been developed and extensively applied for dynamically downscaling coarse resolution information from different sources, such as general circulation models (GCMs) and reanalyses, for different purposes including past climate simulations and future climate projection. Thus far, the nature, the methods, and a number of crucial issues concerning the use of dynamic downscaling are still not well understood. The most important issue is whether, and if so, under what conditions dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
135
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 212 publications
(143 citation statements)
references
References 141 publications
(184 reference statements)
2
135
0
1
Order By: Relevance
“…It is worth noting that SDII is projected to increase by both models in all subregions. Generally, major model biases in simulating present-day climate would be systematically propagated into future climate projections at regional scales [Liang et al, 2008;Xue et al, 2014]. A more accurate simulation of present-day climate provides confidence that future projections are more credible.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that SDII is projected to increase by both models in all subregions. Generally, major model biases in simulating present-day climate would be systematically propagated into future climate projections at regional scales [Liang et al, 2008;Xue et al, 2014]. A more accurate simulation of present-day climate provides confidence that future projections are more credible.…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach would allow a broader understanding of the impact of burned areas on surface hydrology, albedo, atmospheric circulation, and precipitation, which is difficult to accomplish via remote sensing and observation studies alone. Moreover, studies have demonstrated that regional climate models provide a reliable tool to study atmospheric circulations and land/atmosphere interactions at spatial scales beyond current general circulation model capabilities Xue 2011, 2013;Xue et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A number of former studies have shown that the results from the DDM were sensitive to different parameters, especially for convective scheme, domain size, and location (Jones et al 1995;Seth and Giorgi 1998;Hong and Pan 2000). The different model setups were very sensitive to a certain climate condition; however, the comprehensive comparisons studies for several factors were relatively weak (Xue et al 2014). In this study, the sensitive experiments indicated that the combinations of model physics schemes and grid sizes were crucial for the model's dynamic downscaling ability.…”
Section: Conclusion and Discussionmentioning
confidence: 86%
“…The RCMs have been widely used for both past climate simulations (Chou et al 2002;Iizuka 2010;De Sales and Xue 2013) and future climate projection (Liang et al 2008;Chen et al 2010;Boberg and Christensen, 2012;Mearns et al 2012;Yu and Wang 2013). However, many issues related to the downscaling capability of this method usually cause skepticism for the application of RCMs (Laprise et al 2000;Castro et al 2005;Rockel et al 2008;Xue et al 2014), mainly because it is unclear that whether the DDM is really capable of adding more climate information at different scales compared with the GCM results or reanalysis, especially for long-term run, and if so under what conditions?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation